2010
DOI: 10.1002/eji.201040490
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxins of the human pathogen Aeromonas hydrophila trigger, via the NLRP3 inflammasome, caspase‐1 activation in macrophages

Abstract: Aeromonas hydrophila is a Gram-negative pathogen that causes serious infectious disease in humans. A. hydrophila induces apoptosis in infected macrophages, but the host proinflammatory responses triggered by macrophage death are largely unknown. Here, we demonstrate that the infection of mouse macrophages with A. hydrophila triggers the activation of caspase-1 and release of IL-1b. Caspase-1 activation was abrogated in macrophages deficient in Nod-like receptor family, pyrin domain containing 3 (NLRP3) and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…However, we recently demonstrated that A. hydrophila-mediated caspase-1 activation and IL-1b secretion in BMM was orchestrated by three poreforming toxins (aerolysin, hemolysin, and MARTX) (30). Of these three pore-forming toxins we were only able to identify a homologous aerolysin gene in our A. veronii strain (data not shown).…”
Section: A Veronii-inducing Caspase-1 Activation Is Dependent On Botmentioning
confidence: 77%
“…However, we recently demonstrated that A. hydrophila-mediated caspase-1 activation and IL-1b secretion in BMM was orchestrated by three poreforming toxins (aerolysin, hemolysin, and MARTX) (30). Of these three pore-forming toxins we were only able to identify a homologous aerolysin gene in our A. veronii strain (data not shown).…”
Section: A Veronii-inducing Caspase-1 Activation Is Dependent On Botmentioning
confidence: 77%
“…5B and C), suggesting that the presence of LPS in the bloodstream, which may occur after structural or functional damage to the colon associated with S. dysenteriae serotype 1 or STEC infections, augments proinflammatory cytokine production, leading to increased localized vascular damage. Among numerous inflammasome activators, the NLRP3 inflammasome is strongly activated by a large number of bacterial toxins (63)(64)(65)(66). One important conceptual question that remains to be addressed is whether receptor-mediated internalization of Stxs or the retrotranslocation of functional StxA1 fragments across the ER membrane could be recognized by cytosolic receptors such as NLR inflammasome sensors.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different types of inflammasomes, which are distinguished by their nucleotide-binding oligomerization domain-like receptor (NLRs), adaptors, and stimuli specificity. The NLR family pyrin domain-containing 3 (Nlrp3) inflammasome is activated by endogenous and exogenous stimuli, including the accumulation of uric acid crystals and silica, pore-forming bacterial toxins, b-amyloid, low potassium concentrations, and intracellular reactive oxygen species (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%